The Effect of Economic Growth, Unemployment, and Savings on Interest Rates and Inflation (Efficient: Indonesian Journal of Development Economics, 2022)
Inflation, interest rates, savings, economic growth, and unemployment are macroeconomic fundamental variables that are important and mutually influential and must remain stable. The purpose of this study is to determine the direct, indirect, and total effect of economic growth, unemployment and savings on interest rates and inflation in Indonesia. The method of analysis used multiple regression standard model and path analysis. The type of data used is secondary time series data for 33 years (1986-2019) obtained from BPS and the World Bank. The main research results show that macroeconomic fundamental variables; saving, economic growth and unemployment have a negative and significant effect both directly on inflation and indirectly through interest rates on inflation. The first largest contribution is from economic growth, and the smallest contribution is from the unemployment variable. This research provides policy implications to maintain macroeconomic stability, first of all to increase high and quality economic growth and maintain low unemployment. Inflasi, suku bunga, tabungan, pertumbuhan ekonomi, dan pengangguran merupakan variabel fundamental makro ekonomi yang penting dan saling berpengaruh serta harus tetap dapat dijaga stabilitasnya. Tujuan penelitian ini untuk mengetahui pengaruh langsung, pengaruh tidak langsung dan pengaruh total dari pertumbuhan ekonomi, pengangguran dan tabungan terhadap suku bunga dan inflasi di Indonesia. Metode analisis digunakan regresi berganda model baku dan path analysis. Jenis data digunakan data sekunder time series selama 33 tahun (1986-2019) yang diperoleh dari BPS dan World Bank. Hasil riset utama menunjukkan bahwa variabel fundamental makro ekonomi; tabungan, pertumbuhan ekonomi dan pengangguran berpengaruh negatif dan signifikan baik secara langsung terhadap inflasi dan secara tidak langsung melalui tingkat suku bunga terhadap inflasi. Kontribusi pengaruh terbesar pertama diberikan dari pertumbuhan ekonomi, dan sumbangan terkecil dari variabel pengangguran. Riset ini memberikan implikasi kebijakan untuk menjaga stabilitas ekonomi makro, terlebih dahulu harus ditingkatkan pertumbuhan ekonomi tinggi dan berkualitas serta menjaga pengangguran yang rendah.